2021
DOI: 10.1186/s13048-021-00919-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-149-3p promotes the cisplatin resistance and EMT in ovarian cancer through downregulating TIMP2 and CDKN1A

Abstract: Background Ovarian cancer (OC), a kind of gynecological cancer, is characterized by high mortality rate, with microRNAs (miRNAs) playing essential roles in it. However, the clinical significance of miRNAs and their molecular mechanisms in OC are mostly unknown. Methods miR-149-3p expression was predicted through Gene Expression Omnibus (GEO) data in OC and confirmed by q-PCR in various OC cells and tissues from patients with different clinical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 32 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…TIMP2 was a kind of matrix metalloproteinases (MMP) inhibitor, while MMPs were intriguing genes frequently up-regulated in most cancers ( Gobin et al, 2019 ). Consistent with theoretical expectations, as an MMP inhibitor, TIMP2 was downregulated in many cancer types, and its high expression may indicate a better prognosis ( Stetler-Stevenson and Gavil, 2014 ; Wang et al, 2021 ; Wang and Liu, 2021 ). In our research, we found that both TIMP2 mRNA and protein expression were negatively correlated with miR-483-5p.…”
Section: Discussionsupporting
confidence: 80%
“…TIMP2 was a kind of matrix metalloproteinases (MMP) inhibitor, while MMPs were intriguing genes frequently up-regulated in most cancers ( Gobin et al, 2019 ). Consistent with theoretical expectations, as an MMP inhibitor, TIMP2 was downregulated in many cancer types, and its high expression may indicate a better prognosis ( Stetler-Stevenson and Gavil, 2014 ; Wang et al, 2021 ; Wang and Liu, 2021 ). In our research, we found that both TIMP2 mRNA and protein expression were negatively correlated with miR-483-5p.…”
Section: Discussionsupporting
confidence: 80%
“…Cells were cultured in Dulbecco modified Eagle’s culture medium containing 10% fetal bovine serum (Gibco, Carlsbad, California) in an incubator with 5% carbon dioxide at 37°C. Drug-resistant cell lines SKOV3 and A2780 were constructed by treating the proliferated cell cultures using DDP (Meilun Biotech, Dalian, China) at a concentration of 8 μM for consecutive 12 weeks [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression of miR-363 was also decreased, promoting EMT by attenuating the direct inhibitory effect on Snail (83, 84). In contrast, the expression of miR-149-3p was increased, promoting EMT by downregulating TIMP2 and CDKN1A expression (85). Notably, in OC cells, there is a miR-374b-5p-FOXP1 feedback loop in which miR-374b-5p can negatively regulate FOXP1 by binding to the 3'UTR of FOXP1, which can also repress miR-374b-5p transcription.…”
Section: Long Non-coding Rnasmentioning
confidence: 98%